Concrete Structures Under Projectile Impact - Fang, Qin.; Wu, Hao.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
In this book, the authors present their theoretical, experimental and numerical investigations into concrete structures subjected to projectile and aircraft impacts in recent years. Innovative approaches to analyze the rigid, mass abrasive and eroding projectile penetration and perforation are proposed. Damage and failure analyses of nuclear power plant containments impacted by large commercial aircrafts are numerically and experimentally analyzed. Ultra-high performance concrete materials and structures against the projectile impact are developed and their capacities of resisting projectile impact are evaluated. This book is written for the researchers, engineers and graduate students in the fields of protective structures and terminal ballistics.
Introduction -- Impact phenomenon and existing studies -- Rigid projectile impact -- Mass abrasive projectile penetration -- Terminal ballistic trajectory -- Numerical simulation -- New types of concrete materials under projectile impact -- New types concrete structures under projectile impact -- Aircraft impact on Nuclear Power Plant containment -- Future works.
Keywords: Building materials; Mechanics, Applied; Security systems; Building Materials; Engineering Mechanics; Security Science and Technology; Structural Materials